Publicidad de alimentos ultra procesados en youtubers preescolares durante la COVID-19: estudio de caso - Dra. Alba LÓPEZ BOLÁS,Dra. Beatriz FEIJOO FERNÁNDEZ,Dra. Erika FERNÁNDEZ GÓMEZ (Fonseca, Journal of Communication, 2023)
Extended crises in which preschool audiences increase their screen time and their eating habits are negatively affected should bring about the enforcement of stricter controls over covert advertising. This article aims to identify and analyze covert advertising for ultra-processed food brands posted by popular child YouTubers Vlad and Niki during the COVID-19 state of alarm.